RETRACTION: Pengaruh Pengetahuan Peraturan Perpajakan Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak KPPP Bandung Karees - Dwi Anggraeni Saputri; Ela Sulistia (Competitive, 2020)
RETRACTION TO: Saputri, D. A., & Sulistia, E. (2019). Pengaruh Pengetahuan Peraturan Perpajakan Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak KPPP Bandung Karees. Jurnal Competitive, LPPM Politeknik Pos Indonesia. Volume 14 Nomor 2. (60-71). Nomor DOI: 10.36618/competitive.v14i2.620. This article has been retracted by the publisher based on the following reason: This is based on the editor that the author has committed acts of violation of publication ethics. The author has published a double publication by submitting the same article to two journals before. The author admits that he forgot to have submitted the same article to another journal. This article also has published in the Open Library Telkom University (https://openlibrary.telkomuniversity.ac.id/pustaka/140440/pengaruh-pengetahuan-peraturan-perpajakan-dan-kualitas-pelayanan-terhadap-kepatuhan-wajib-pajak-pada-kantor-pelayanan-pajak-pratama-bandung-karees-kasus-pada-wajib-pajak-orang-pribadi-pada-kpp-pratama-bandung-karees-.html). One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere, and also not considered by another journal. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter, and apologies are offered to readers of the journal that this was not detected during the submission process.